The Challenges Facing the Multilateral Trading System in Addressing Global Public Policy Objectives - Christophe Bellmann; Jonathan Hepburn; Marie Wilke (Revue Internationale de Politique de Développement)
Despite a record-breaking 14.5 per cent increase in world merchandise exports, the effects of the financial crisis and global recession are still hampering faster economic recovery. Relatively high oil prices combined with persistent unemployment and measures designed to reduce budget deficits have undermined short-term growth prospects. While South–South trade continues to explode, trade imbalances – i.e. the gap between exports and imports – widened in 2010 compared to 2009 (though smaller than pre-crisis levels). Meanwhile, trade negotiations under the Doha Round have reached an impasse, generating uncertainties about the future of the World Trade Organization (WTO) as a negotiating forum. Under these circumstances, should the system rethink its decision-making process founded upon the predominance of member states, the principle of consensus and the notion of single undertaking, as some critics have suggested? And, if so, how could such a reform agenda be initiated at the WTO? Moreover, beyond the negotiating function of the WTO, the paralysis of the system also raises urgent questions about the ability of the system to respond to pressing challenges of our times, such as trade and climate change, or food security and price volatility.